Use of Recombinant Mitogillin for Improved Serodiagnosis of Aspergillus fumigatus-Associated Diseases - Weig, Michael (American Society for Microbiology, 2001)
During human infection, Aspergillus fumigatus secretes a 18-kDa protein that can be detected as an immunodominant antigen in the urine of infected patients. Recently, this protein was shown to be mitogillin, a ribotoxin that cleaves a single phosphodiester bond of the 29S rRNA of eukaryotic ribosomes. We proved the immunogenic capacity of mitogillin in a rabbit animal model, indicating its usefulness as an antigen for serological diagnosis of invasive aspergillosis. The mitogillin gene from A. fumigatus was transferred from plasmid pMIT+ to expression vector pQE30 and expressed in Escherichia coli as a fusion protein. Purified recombinant mitogillin was recognized by serum immunoglobulin G (IgG) of polyclonal rabbit sera that were obtained by immunization with purified native mitogillin. Consequently, we developed an enzyme-linked immunosorbent assay for detection of IgG, IgM, and IgA antibodies to recombinant mitogillin. In serum samples of patients suffering from aspergilloma (AO; n = 32), invasive pulmonary aspergillosis (IPA; n = 42), or invasive disseminated aspergillosis (IDA; n = 40), a good correlation of production of IgG antibody against mitogillin and clinical disease was observed (for patients with AO, 100% [32 of 32] were positive; for patients with IPA, 64% [31 of 42] were positive; for patients with IDA, 60% [24 of 40] were positive). In contrast, positive titers for serum IgG and IgM antibodies against mitogillin were found in only 1.3% of the serum samples of healthy volunteers and positive titers for IgA antibody were found in only 1.0% of the serum samples of healthy volunteers (n = 307; specificity = 95.4%). These results indicate that recombinant mitogillin expressed in E. coli can be used for improvement of the serodiagnosis of A. fumigatus-associated diseases.